Analysis of resistive termination in high speed digital design - Siew, Cynthia Xin Ya. (2009)
High speed design suffers from serious signal integrity issues, resulting in distortion of the high speed signals and leading to unreliable operation. Signal integrity issues occur due to many reasons; however, it is ringing in high speed digital circuits which distort the signal most severely. Unreliable operation occurs because the distorted signals cause erroneous and false switching in high speed circuits. The main focus in this report is to understand the causes for ringing in high speed signals, as well as to evaluate different solutions to minimize ringing in active circuits. In order to investigate ringing, a trace is first studied. Next, ringing in an active clock driver is investigated, and finally, different techniques are evaluated to minimize the ringing in actual systems.